2010
DOI: 10.5045/kjh.2010.45.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Image analytic study of nuclear area in mantle cell lymphoma

Abstract: BackgroundMalignant lymphomas are classified on the basis of morphology, immunohistochemistry, and genetic and molecular biological features. Morphology is considered the most important and basic feature. Lymphomas can be classified as small, medium, or large depending on the cell size, but this criterion tends to be rather subjective. The aim of this study was to investigate the usefulness of an objective approach based on quantitative measurements.MethodsTwenty specimens of mantle cell lymphoma and 2 specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, no other morphometric parameters were analyzed in that study, and correlation with survival was not investigated. 35 Compared to classic MCL, we found that 16 and 13 morphometric parameters related to nuclear size and shape were significantly different in blastoid and pleomorphic MCL, respectively (Table 3). Both aggressive variants had higher mean, higher variance, lower skewness, and/or lower kurtosis of nuclear length, width, perimeter, area, and/or irregularity.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, no other morphometric parameters were analyzed in that study, and correlation with survival was not investigated. 35 Compared to classic MCL, we found that 16 and 13 morphometric parameters related to nuclear size and shape were significantly different in blastoid and pleomorphic MCL, respectively (Table 3). Both aggressive variants had higher mean, higher variance, lower skewness, and/or lower kurtosis of nuclear length, width, perimeter, area, and/or irregularity.…”
Section: Discussionmentioning
confidence: 80%
“…[32][33][34] Later on, a study showed that the nuclear area of MCL tumor cells was significantly larger than that of mantle zone lymphocytes in reactive tonsils. 35 No cases with blastoid/pleomorphic morphology were included in that study, and their mean nuclear area of MCL measured with manual annotation by three pathologists was 37.9 μm 2 , 37.9 μm 2 , and 38.2 μm 2 , respectively. 35 Their result was similar to that of our classic MCL (42.42 μm 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation